ANALISIS FAKTOR PENGHAMBAT PENEGAKAN HUKUM PIDANA DI INDONESIA DALAM PERSPEKTIF TEORI LAWRENCE FRIEDMAN - Yusuf DM, Mohd.; Saragih, Geofani Milthree; Setiawan, Feri; Sitompul, Hasran Irawadi; Berson, Hendri (Universitas Labuhanbatu, 2025)
This study aims to analyze the factors hindering law enforcement in Indonesia through the perspective of Lawrence Friedman's legal system theory, which consists of legal structure, legal substance, and legal culture. The research employs a normative legal method with statutory and conceptual approaches. Data were analyzed from primary and secondary legal materials and correlated with relevant empirical practices. The findings reveal that the main obstacles to law enforcement lie in the lack of integrity and professionalism among law enforcement officials, inconsistencies in legal substance, and the generally low level of legal culture in society. Low legal awareness and a preference for informal dispute resolution further weaken the formal legal system. This study recommends structural reforms of law enforcement institutions and the enhancement of legal culture through legal education and consistent, fair law enforcement. Keywords: Legal Structure; Legal Substance; Legal Reform; Public Legal Awareness.